Some physical and thermal properties of the composite (Basalt-Aluminum) prepared by powder technology method. - Jassim, Ismail Khalil; Abdel Aziz, Abdel Samie Fawzi; Darwish, Saleh Younis (Journal of natural sciences, life and applied sciences, 2018)
Used in the paper basalt rock powder is matrix and reinforcement it by aluminum powder at ratios (0%,10%,20%,30%,40%,50%), mixing the matrix and reinforcement material and pressing at (4 ton) at two min. only. Treatment thermal was at (1000 ˚C) at a vacuum of oxygen. At period of time two hours only . take place the density physical test after and before sintering and density theoretical for prepared sample, as for the thermal tests included (thermal conductivity, thermal effusion, thermal diffusion, thermal capacity, thermal resistance). By using (Mathis TCi). shown result of density increasing of density after sintering and a close from theoretical density to (2.6 g/cm3) at ration 50% aluminum, while shown results the thermal tests enhancement clear in and thermal diffusion to composite and increasing in thermal conductivity values to (3.7 w/m.k) and thermal diffusion to (3.1643mm2/sec) and thermal effusion to (2080 w.s1/2/m2.k) with increasing proportion of aluminum additives to 50% aluminum. While heat capacity values decreased with increasing reinforcement to 50% aluminum.
Keywords: thermal diffusion; powder technology; basalt composites; composite materials